2017
DOI: 10.22266/ijies2017.0831.04
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Field-Oriented Control Using Supervisory Type-2 Fuzzy Control for Dual Star Induction Machine

Abstract: This paper proposes Interval Type-2 Fuzzy Gain-Adaptive PI (IT2FGAPI) controller based on direct field oriented control (DRFOC), to control the speed of a dual star induction machine (DSIM), to get a robust performance machine. We use IT2FGAPI for speed control of the DSIM corresponding to adapting the different gains Kp and Ki corresponding the different PI logic, PI of speed, PI of flux and the four PI of currents in a vector control mode. An interval type-2 fuzzy control system is used to adapt in real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…DFIM comprises three stator coils and three rotor coils offset by an identical distribution angle. Vectors equations of voltages, currents and total stator and rotor fluxes are given as follow [6]:…”
Section: Mathematical Machine Modelmentioning
confidence: 99%
“…DFIM comprises three stator coils and three rotor coils offset by an identical distribution angle. Vectors equations of voltages, currents and total stator and rotor fluxes are given as follow [6]:…”
Section: Mathematical Machine Modelmentioning
confidence: 99%
“…To solve the problem of 𝜑 1 (x 1 , 𝑘) and 𝜑 2 (x 1 , x 2 , 𝑘) , we approximate them by a two-interval type-2 fuzzy adaptive systems. A fuzzy system that uses fuzzy type 2 sets and inference is a fuzzy type 2 system [10][11][12][13][14][15][16]. Type-1 fuzzy set has a crisp membership degree, while type-2 fuzzy set (T2FS) has a fuzzy membership degree.…”
Section: Interval Type-2 Fuzzy Adaptive Controlmentioning
confidence: 99%
“…The fuzzy logic control based on Type 2 Fuzzy Sets (T2-FS) present a suitable solution for the control of non-linear systems [29]. T2-FS were first proposed in [33][34][35] as an extension to Type 1 Fuzzy Sets (T1-FS), to increase the fuzziness of the relations. Several studies have shown the high performance of T2-FLC, which uses the T2-FS interval instead of Type 1 FLC (T1-FLC) in terms of handling the uncertainties [17,28,34].…”
Section: Type 2 Fuzzy Logic Controllermentioning
confidence: 99%